2007
DOI: 10.1159/000297738
|View full text |Cite
|
Sign up to set email alerts
|

Transient Visual Loss Triggered by Scuba Diving in a Patient with a Petrous Epidermoid and Combined Thrombotic Risk Factors

Abstract: A 25-year-old woman who developed transient neurological abnormalities after scuba diving is reported. The subsequent day she experienced transient left-side monocular blindness. Arterial ocular occlusion in apparently healthy young women is unusual, and a search for the cause of this devastating vascular event is mandatory. Occlusion of the left branch retinal artery, total occlusion of the left internal carotid artery, and a petrous apex epidermoid were found, together with a shortened prothrombin time (INR:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The ineffectiveness of anticoagulation and the alternate surprisingly effective treatment and prophylaxis with antiplatelet drugs have since also been observed by others. [29][30][31] The inability of standard anticoagulants to directly influence platelet aggregation is believed to be the most plausible explanation of this phenomenon.…”
Section: The Discovery Of Sps: From Its Initial Description To Full Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The ineffectiveness of anticoagulation and the alternate surprisingly effective treatment and prophylaxis with antiplatelet drugs have since also been observed by others. [29][30][31] The inability of standard anticoagulants to directly influence platelet aggregation is believed to be the most plausible explanation of this phenomenon.…”
Section: The Discovery Of Sps: From Its Initial Description To Full Cmentioning
confidence: 99%
“…The concomitant occurrence of SPS with other well-defined thrombophilias (elevated factor VIII, antiphospholipid syndrome, prothrombin G20201A, and hyperhomocysteinemia) were subsequently reported. 29,[33][34][35][36][37] In fact, as shown by Ruiz-Argüelles et al, most patients with SPS phenotype might display other thrombophilic conditions, both inherited and acquired. Thus, the coexistence of SPS with other conditions may be required in some cases for the development of vaso-occlusive episodes and clinical manifestation, in accordance with the concept of multifactorial thrombophilia.…”
Section: The Discovery Of Sps: From Its Initial Description To Full Cmentioning
confidence: 99%
“…The recurrence of thrombosis during adequate anticoagulation therapy with low-molecular-weight-heparin (LMWH) or vitamin K antagonists (VKA) is an interesting clinical feature, reported by several authors. 14,23,27,28 The patient with initial venous thrombosis or pulmonary embolism (PE), under efficient anticoagulation treatment (e.g., therapeutic prolongation of prothrombin time in case of VKA) and suffering from the arterial or new venous thrombosis in a short time (few months) after the first event, represents a typical scenario. The inability of conventional anticoagulation drugs to directly inhibit platelet functions is regarded as a cause.…”
Section: Clinical Manifestation and Diagnosis Of Sticky Platelet Syndmentioning
confidence: 99%
“…After the first such report by Chaturvedi and Dzieczkowski in 1999 of a young woman with recurrent stroke, protein S deficiency, activated protein C resistance (APCR) caused by heterozygous factor V Leiden, and SPS, 24 other cases of combined thrombophilia (with elevated FVIII activity, antiphospholipid syndrome, prothrombin G20201A polymorphism, hyperhomocysteinemia) were published. 21,25,26,32,34,40 Of note, a larger study by Ruiz-Argüelles et al found combined thrombophilia in the majority of patients with platelet hyperagregability. 28…”
Section: Further Clinical and Laboratory Characterization Of Sticky Pmentioning
confidence: 99%
“…Further evidence for a good efficacy of ASA, although mostly in a limited number of patients, was provided by other authors in later years. [18][19][20][21][22][23][24][28][29][30][31][32][33][34][35][36][37][38][39][40] Data on other antiplatelet agents are scarce.…”
Section: Treatment Approach To Sticky Platelet Syndromementioning
confidence: 99%